2020
DOI: 10.3892/mco.2020.2054
|View full text |Cite
|
Sign up to set email alerts
|

Long‑term outcomes of incidental gallbladder carcinoma without additional resection: A single institution experiment

Abstract: Incidental gallbladder carcinoma (IGC), defined as unexpected malignancy identified in the surgical gallbladder specimen of a cholecystectomy performed for a benign diagnosis, can be difficult to suspect preoperatively. Furthermore, there are valid clinical reasons to defer reoperation for additional resection, particularly in elderly patients. The present study aimed to determine the long-term outcomes and prognostic factors associated with recurrence in patients with IGC. The medical records of 678 patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…A significant benefit of re-resection of gallbladder bed and regional lymph nodes following incidental gallbladder cancer was observed, especially with pT2 and pT3 disease [10]. On the other hand, another study observed that in their 12 incidental gallbladder cancers, long term survival was achieved without additional resection even in pT2 and T3 disease [11]. In our case, the patient was metastatic by the time she returned for further follow up, so there was no indication for further surgical intervention.…”
Section: Discussionmentioning
confidence: 48%
“…A significant benefit of re-resection of gallbladder bed and regional lymph nodes following incidental gallbladder cancer was observed, especially with pT2 and pT3 disease [10]. On the other hand, another study observed that in their 12 incidental gallbladder cancers, long term survival was achieved without additional resection even in pT2 and T3 disease [11]. In our case, the patient was metastatic by the time she returned for further follow up, so there was no indication for further surgical intervention.…”
Section: Discussionmentioning
confidence: 48%
“…This was consistent with a Japanese study. 30 The bad prognosis can be explained by the age of the participants at admission, dispersal of tumor cells into the liver bed through the ducts of Luschka and peritoneal cavity, and recurrence from the cystic duct stump. However, another study showed a better prognosis as their treatment modality constituted aggressive curative resection including radical cholecystectomy together with right hepatectomy and bile duct reconstruction.…”
Section: Discussionmentioning
confidence: 99%
“…Early GBCs have more favorable outcomes, but they do not have specific symptoms, so they are mostly discovered incidentally, usually on histopathological ex-amination of the gallbladder specimen after cholecystectomy is performed for a benign diagnosis. [1][2][3][4] Laparoscopic cholecystectomy (LC) is one of the most often performed general surgeries. Incidental gallbladder carcinoma (IGBC) is diagnosed in 0.3-2.9% of all cholecystectomies and accounts for the majority of detected GBCs.…”
Section: Introductionmentioning
confidence: 99%
“…Pathological examinations after cholecystectomy are essential in the diagnosis of GBC. [2][3][4] This study aims to evaluate the incidence, clinical characteristics, and prognostic features of IGBC diagnosed after LC for benign gallbladder disease in rural areas.…”
Section: Introductionmentioning
confidence: 99%